Enhancing Teacher Professionalism Through Educational Supervision: A Literatur Review In Indonesian Context - Hilhamsyah Hilhamsyah; Ridho Azahar; Pan Surya Handika (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Educational supervision plays an important role in improving the quality of teacher professionalism in schools. The reality in Indonesia is that supervision is not well understood in terms of its function and purpose. In addition, supervision is still administrative in nature and has not focused on improving teacher professionalism. This research aims to reveal the implementation strategies of educational supervision that can improve teacher professionalism. This research method uses a literature study using Google Scholar data base indexed sinta 1 to 3 published in 2019-2024 using the keywords supervision, teacher, professionalism based on research topics that are relevant to the research objectives. The results showed that 1) strategies that can be used in educational supervision are the contribution of school principals, e-supervision-based and collaborative approaches. 2) The characteristics of teacher professionalism are dedicated, competent, communicative and integrity. With this research, it is hoped that it can contribute to making a supervision policy programme that focuses on developing teacher professionalism in educational institutions